# Solve for z 2(4z-8)=6(z+6) 2(4z-8)=6(z+6)
Simplify 2(4z-8).
Apply the distributive property.
2(4z)+2⋅-8=6(z+6)
Multiply.
Multiply 4 by 2.
8z+2⋅-8=6(z+6)
Multiply 2 by -8.
8z-16=6(z+6)
8z-16=6(z+6)
8z-16=6(z+6)
Simplify 6(z+6).
Apply the distributive property.
8z-16=6z+6⋅6
Multiply 6 by 6.
8z-16=6z+36
8z-16=6z+36
Move all terms containing z to the left side of the equation.
Subtract 6z from both sides of the equation.
8z-16-6z=36
Subtract 6z from 8z.
2z-16=36
2z-16=36
Move all terms not containing z to the right side of the equation.
Add 16 to both sides of the equation.
2z=36+16
Add 36 and 16.
2z=52
2z=52
Divide each term by 2 and simplify.
Divide each term in 2z=52 by 2.
2z2=522
Cancel the common factor of 2.
Cancel the common factor.
2z2=522
Divide z by 1.
z=522
z=522
Divide 52 by 2.
z=26
z=26
Solve for z 2(4z-8)=6(z+6)

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top